Chronic antioxidant therapy lowers blood pressure in adult but not in young Dahl salt hypertensive rats: the role of sympathetic nervous system - Vaněčková, I; Vokurková, M; Rauchová, H; Dobešová, Z; Pecháňová, O; Kuneš, J; Vorlíček, J; Zicha, J (Acta physiologica, 2013)
AIM: It is well-known that salt hypertension is associated with increased oxidative stress. Since the development of salt hypertension is age-dependent, we were interested whether young and adult salt hypertensive Dahl rats differ in oxidative stress level and/or in the effects of chronic antioxidant therapy on blood pressure (BP) level and on the participation of particular vasoconstrictor/vasodilator systems in BP maintenance. METHODS: Young (5-week-old) and adult (12-week-old) salt-sensitive (Dahl-S) male rats were fed high-salt diet (5% NaCl) and drank tempol solution (2 mm) for 5 weeks. BP was monitored with radiotelemetry and vasoconstrictor/vasodilator balance was evaluated at the end of experiment. Moreover, NO synthase activity, superoxide production and lipoperoxidation were determined in heart, kidney and aorta in separate subgroups of Dahl rats. RESULTS: Tempol treatment had quite opposite BP effects in young and adult Dahl-S rats. While it tended to increase BP in young salt hypertensive Dahl-S rats, it significantly lowered BP in the adult ones due to reduced sympathetic vasoconstriction. Importantly, high salt intake substantially reduced NO synthase activity in heart and kidney, and markedly increased superoxide production in kidneys and aorta of adult Dahl-S rats in which BP correlated positively with superoxide production in thoracic aorta and lipoperoxidation in kidneys. CONCLUSION: Chronic antioxidant therapy lowered BP only in adult salt hypertensive Dahl-S rats in which superoxide levels were increased in both kidneys and aorta. Blood pressure reduction induced by chronic tempol treatment is related to attenuated sympathetic vasoconstriction rather than to augmented NO-dependent vasodilatation.
Keywords: Oxidative Stress; oxidační stres; Cyclic N-Oxides; Hypertension; chlorid sodný; stárnutí; krysa rodu Rattus; spinové značení; sympatický nervový systém; Antioxidants; zvířata; Aging; Rats, Inbred Dahl; antioxidancia; krevní tlak; Male; hypertenze; Rats; cyklické N-oxidy; Animals; Sodium Chloride; mužské pohlaví; Spin Labels; Sympathetic Nervous System; Blood Pressure; potkani inbrední Dahl